Plasmonic and electronic characteristics of (Zr,Nb)Nx thin films with different metal content - Tianrun, Wang; Yujing, Ran; Tingting, Liu; Qian, Guo; Chang, Gao; Zhaotan, Jiang; Zhi, Wang (Applied physics. A, Materials science & processing, 2022)
As a kind of conductive ceramic, transition metal nitrides are regarded as alternative plasmonic materials to noble metals, mainly because of their high melting point and tunability. Ternary nitride (nitride of alloy), is higher tunable because of its tunable metal content. In this work, (Zr,Nb)N x ternary nitride thin films of zirconium and niobium with different metal content were prepared by DC magnetron sputtering. Structural, plasmonic and electronic properties of the films were studied. The results show that the films are in rock salt structure, and increased Zr content can enlarge the lattice constant. The thin films exhibit metallic and dielectric in different wavelength range, and increased Zr content can reduce the screened plasma frequency. Nb-rich films show dual epsilon-near-zero characteristic. The dielectric characteristic of the films is related to the intraband and interband transition of the electrons, which is confirmed by calculated band structures. The calculations show that increased Zr content lowers the characteristic energy levels at which interband transition is excited. For its high tunability, (Zr,Nb)N x can be applied in extensive fields.